Analisis Pengaruh Tingkat Religiusitas, Peer Influence, Dan Literasi Keuangan Syariah Terhadap Minat Investasi Mahasiswa Di Pasar Modal Syariah - Nasution, Azli Azumar; Imsar, Imsar; Hasibuan, Faisal Umardani (Jambura Economic Education Journal, 2026)
This study analyses the influence of spiritual beliefs, peer pressure, and Sharia financial literacy on the investment interest of FEBI UINSU students in the Sharia capital market. Using a quantitative approach with SmartPLS, the results demonstrate that all three variables have a positive and significant impact. Sharia financial literacy emerged as the dominant factor (t=3.835; p=0.000), followed by religiosity (t=3.353; p=0.001) and peer influence (t=3.322; p=0.001). An adjusted R-squared value of 0.634 indicates that these independent variables account for 63.4% of the variation in students' investment interest. This confirms that the synergy between Islamic values, social interaction, and financial understanding is key to their involvement in Sharia investment.